1978
DOI: 10.1149/1.2131715
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology of GaAs Layers Grown by Electroepitaxy and Thermal LPE

Abstract: It was found that terraces commonly present on GaAs layers grown by standard (thermal) LPE were not present on layers grown by electroepitaxy. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Under electromigration control it has been shown that growth takes place under nearly equilibrium (isothermal) conditions (11) Consistent with this result it has been found that the surface morphology of electroepitaxial layers (attained under electromigration control) do not exhibit terracing commonly observed on layers grown by standard (thermal) LPE (12). In the light of these results, the present study was undertaken and aimed at the comparison of the defect structure and electrical properties of GaAs layers grown by thermal cooling and by electromigration controlled electroepitaxy under similar over-all conditions.…”
mentioning
confidence: 60%
“…Under electromigration control it has been shown that growth takes place under nearly equilibrium (isothermal) conditions (11) Consistent with this result it has been found that the surface morphology of electroepitaxial layers (attained under electromigration control) do not exhibit terracing commonly observed on layers grown by standard (thermal) LPE (12). In the light of these results, the present study was undertaken and aimed at the comparison of the defect structure and electrical properties of GaAs layers grown by thermal cooling and by electromigration controlled electroepitaxy under similar over-all conditions.…”
mentioning
confidence: 60%
“…The current can create a temperature gradient by a combination of Peltier cooling/ heating or resistive heating, and also enhances solute mass transfer by electromigration [142,143] [144]; [145] [146][147][148][149][150][151][152][153][154][155][156]; and [81]; and [157]. The current can create a temperature gradient by a combination of Peltier cooling/ heating or resistive heating, and also enhances solute mass transfer by electromigration [142,143] [144]; [145] [146][147][148][149][150][151][152][153][154][155][156]; and [81]; and [157].…”
Section: Liquid-phase Electroepitaxymentioning
confidence: 99%
“…In our earlier work [1] we have reported the growth of the quaternary layers by the liquid phase electroepitaxial (LPEE, also known as current controlled liquid phase epitaxy) technique. LPEE has the advantage that as the growth is controlled by an external parameter (electric current), uniformity in epilayer thickness and composition [ 2,3], interface stability [4] and the epilayer surface morphology [5] are better than those grown by the conventional LPE techniques. Further, this technique provides limited control on the dopant segregation [6] and the defect structure [7].…”
Section: Introductionmentioning
confidence: 99%